Determinan kesejahteraan Masyarakat Provinsi Sumatera Barat - Ilham Jaya Kusuma; Anis, Ali (Universitas Negeri Padang, 2024)
This study aims to determine the effect of: (1) Education Sector Government Spending, (2) Health Sector Government Spending, (3) Investment, and (4) Income Distribution Disparity on Community Welfare. This research uses panel data analysis methods. The results in this study show that Government Expenditure in the Education Sector and Investment has a positive and significant effect on Community Welfare. Meanwhile, government expenditure in the health sector has a positive but insignificant effect on community welfare. Meanwhile, income distribution disparity has a negative but insignificant effect on community welfare.